Assessment of the biological durability of oil palm trunk modified with 1,3-dimethylol-4,5-dihydroxy-ethyleneurea (DMDHEU) following subsequent curing at elevated temperatures - Rosli, Siti Nurul Ashikin; Chin, Kit Ling; Lee, Chuan Li; Maminski, Mariusz; Abdullah, Luqman Chuah; Toczylowska-Maminska, Renata (North Carolina State University, 2024)
The biological durability of oil palm trunk modified with 1,3-dimethylol-4,5-dihydroxyethyleneurea (DMDHEU) was tested after subsequent curing at elevated temperatures. The resistance against mold, decay fungi, and subterranean termites was examined. Dimethylol dihydroxyethyleneurea-modified OPT demonstrated improved resistance against mold and decay fungi; however, the effect was lesser on subterranean termite attacks. Oil palm trunk modified with 34% DMDHEU and cured at 160 °C exhibited the most effective reduction in mass loss due to biological degradation compared to the untreated controls. High curing temperature (> 180 °C) caused cracks and ruptured the cell walls, exposing the untreated zone of the OPT to biological attack. As a non-biocidal wood modification, homogeneous dispersion of DMDHEU with adequate concentration and curing temperature is important to fully prevent OPT degradation by wood-destroying fungi and termites. These results provide valuable information for technologists to enhance or streamline the experimental design of combined modification with DMDHEU and thermal treatment, supporting their practical goals. It is recommended to continue research on the leaching of DMDHEU-modified OPT to understand the prevailing effect of DMDHEU on the biological durability of OPT, whether it is due to cross-linking or filler dispersion.